(untitled) (ADVANCED TECHNOLOGIES AND COMPUTER SCIENCE, 2022)
In this article we present the novel model of studying the past problems in present. These problems are very well handled by many authors; however, the result remains unproved. The problems are as follows: Nash equilibria in co-operative games and P versus NP theorem by Stephen Cock. We show that there is a solution for both classical problem in a partial case for “P versus NP”-theorem and co-operative games equilibria for all cases. Since partial case for P-NP problem could be proved by showing that Bellman’s dynamic programming (DP) is the most optimal algorithm for composite tasks and problems. We also show that same equation by Bellman within the pre-defined parameter can be valid for both P and NP classes of problem according to the ordered sets of arbitrary variables which are compound to Bellman’s equation, which was studied well in prior works by the same author, who holds the position of IT-analyst at the present time.